1996
DOI: 10.1111/j.1365-2427.1996.tb01766.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the total phosphorus cycle in some temperate lakes: the response to enrichment

Abstract: 1. Total phosphorus (TP) cycles were examined in seventeen lakes from the Scottish lowlands and Northern Ireland, which varied in annual mean TP from 17 to 192 pg P 1-*. 2. It is clear from the data that the annual range of TP concentrations increases as the annual maximum TP increases. Although the annual minimum TP increases somewhat with increasing annual maxima, even enriched lakes show a pronounced TP minimum. As a result, the annual maximum values are highly correlated with the ranges and means, but less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
1
20
2
5
Order By: Relevance
“…This observation is in contrast to those made about diatom-nutrient relationships where it is has been observed that increases in concentration are associated with substantial increases in range (e.g. Gibson et al, 1996cited in Anderson, 1997.…”
Section: Assessment Of Hypothesiscontrasting
confidence: 79%
“…This observation is in contrast to those made about diatom-nutrient relationships where it is has been observed that increases in concentration are associated with substantial increases in range (e.g. Gibson et al, 1996cited in Anderson, 1997.…”
Section: Assessment Of Hypothesiscontrasting
confidence: 79%
“…in Finnish lakes a 10-year summer average is used) and also seasonal changes in values are not available in this dataset. Gibson et al (1996) indicate that these seasonal variations can be an important factor in the analyses of the interannual trends in trophic status in shallow lakes. Although the general response of well known indicator species seems to hold, there are many species that are classified differently according to the database selection and classification methods.…”
Section: Discussionmentioning
confidence: 98%
“…Although there is substantial published research on the role of organic C in microbial community dynamics, there is less research on the coupling of organic C with the phosphorus cycle, including production of microbial phosphatases, a potentially significant source of phosphate remineralization, especially in aquatic environments (Gibson et al, 1996;Dyhrman et al, 2007;Duhamel and Moutin, 2009;Ruttenberg and Dyhrman, 2012;Duhamel et al, 2014). Because of the potential threats from global warming, considerable research has been done on the coupling of nitrogen and carbon cycles, largely in relation to the effect of nitrogen on primary production, thus enhancing CO 2 sequestration (Esser et al, 2011;Zaehle, 2013).…”
Section: Introductionmentioning
confidence: 99%